Business dynamism and innovation capacity, an entrepreneurship worldwide perspective - Jo\~ao Lopes; Márcio José Sol Pereira Oliveira; Paulo Silveira; Luís M. Carmo Farinha; José Oliveira (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This research aims to identify which factors best explain business dynamics and innovation capacity in the continents of Africa, Asia, Europe, Latin America and the Caribbean, and North America. To achieve this, data from the Global Entrepreneurship Monitor and the Global Competitiveness Report is used. The linear regression method is utilized with the stepwise procedure for data analysis. It is possible to ascertain that, with a view to increasing innovation capacity in the African continent, business leaders and managers should be acquainted with innovation studies to better understand technological advances. In relation to Asia, the detected models of business dynamism and capacity for innovation are positive. On the European continent, the results show that RIS3 has a positive impact on the capacity for innovation. In Latin America and the Caribbean, it seems that business dynamism and the capacity for innovation are negative and regional development policies should be more flexible. In North America, it appears that business dynamism and the capacity for innovation are negative. The research contributes with measures that can be applied by organizations and policymakers to these five continents to improve the performance of business dynamism and the capacity for innovation in their territories. The resulting data give originality to the research as well as important contributions, not only to the theory, but also to the entities (organizations and governments) acting in the field who can implement new policies, such as tax incentives to companies for the first purchase of high-tech equipment, products, or products with intellectual property rights developed by national companies and provide support policies directed to companies that purchase high-tech domestic equipment.
Keywords: 650; entrepreneurship; open innovation; dynamism; GCR; GEM; innovation capability; policies